(untitled) (Journal of Engineering, 2023)
The agricultural lands that depend on supplementary irrigation methods for winter wheat cultivating in wide areas of the Nineveh province are most vulnerable to climate change concerns. Due to frequent rainfall shortages and the temperature increase recently noticed and predicted by the climate scenarios. Hence important to assess the climate effect on the crop response in terms of water consumption during the periods (2021-2040) and (2041-2060) by using high-resolution data extracted from 6 global climate data GCMs under SSP5-8.5 fossil fuel emission scenarios in changing and fixed CO2 concentration. And validate the Aqua-Crop model to estimate the yield and water productivity. And gives the RRSME of 7.1- 4.1 for the calibration and verification, respectively, d and R2 equal 1, indicating good model performance. From findings, the predicted response to the temperature increase and variability in rainfall between increase and decrease represents an increase in irrigation water productivity to 28% in 2060 related to the reference period in the developed schedule under changing CO2 scenario and a reduction by 13% in the near term related to the mid-term under the fixed CO2 concentration scenario. And the simulation of yield production increased by 30 % under the scenario of changing CO2 concentration. While a slight increase of 13 % under the fixed CO2 concentration scenario. These findings help realize the future uncertain resilience of agriculture in Iraq to create efficient adaptation measures to benefit from climate change opportunities.